Legends in consumer behavior - Belk, Russell W. (SAGE Publications, 2014)
The Legends in Consumer Behavior series captures the essence of the most important contributions made in the field of consumer behavior in the past several decades. It reproduces the seminal works of the legends in the field, which are supplemented by interviews of these legends as well as by the opinions of other scholars about their work. The series comprises various sets, each focusing on the multiple ways in which a legend has contributed to the field. This first set in the series, consisting of 10 volumes, is a tribute to Russell W. Belk. Belk is one of the most prolific contemporary consumer behavior and marketing scholars.